AB0654 IMPACT OF GENDER ON PATIENT PROFILE AND TREATMENT RESPONSE IN ANKYLOSING SPONDYLITIS PATIENTS TREATED WITH TNF-α INHIBITORS. (2nd June 2020) - Milic, B.; Ilic, T.; Popovic, M.; Erdeljan, B.; Jankovic, T.
Abstract : Background: Ankylosing spondylitis (AS) was historically seen as a predominantly male disease and although recent data showed a more homogenous sex prevalence there is still a long delay and more often a misdiagnosis in women. Also, studies showed that there might be gender-attributable differences regarding clinical characteristics, radiographic damage and response to treatment. Objectives: The aim of this study was to assess gender differences in AS patients regarding the clinical presentation, disease activity, functional status and response to tumor necrosis factor-alpha inhibitor (TNF-α inhibitor) therapy. Methods: This retrospective analysis included 59 AS patients treated with first TNF-α inhibitor for at least 12 weeks. TNF-α inhibitor therapy introduction and response was determined according to ASAS-EULAR management recommendations for AS. Clinical and demographic parameters were compared between the female and male patients. Results: Twenty-four patients (40, 68%) were females and 35(59, 32%) were males. Women were older than male at moment of study (p=0, 049), at the time of diagnosis (p=0, 05) and when starting biologic therapy (p=0, 009). Moreover, they had a longer diagnosis delay (p=0, 017) compared to men. Prevalence of HLA-B27 status and the rate of peripheral arthritis, dactylitis, enthesitis, uveitis or inflammatory bowel disease (IBD) were not different between two groups. Disease activity and functional status were also similar in both groups. Males had a significantly longer drug survival time for first biologic (p=0, 031). One female patient (4.2%) and 4 male patients (11, 4%) showed primary or secondary inefficacy to TNF-α inhibitor (p=0, 61). All 5 non-responders switched to second TNF-α inhibitor and showed a good clinical response. The comparison of the demographic features, clinical characteristics, disease activity, functional status and response to TNF-α inhibitor therapy according to the gender are presented in Table 1. Conclusion: In our cohort, the presence of the female gender was related to longer diagnosis delay compared to males. Non-response rate for the first TNF-α inhibitor was similar between groups, but men had longer drug survival time for the first biologic. References: [1]Rusman T, van Vollenhoven RF, van der Horst-Bruinsma IE. Gender differences in axial spondyloarthritis: women are not so lucky. Curr. Rheumatol. Rep. 20(6), 35 (2018). [2]Van der Heijde D, Ramiro S, Landewe R, et al. (2017): 2016 update of the ASAS-EULAR management recommendations for axial spondyloarthritis. Ann Rheum Dis.76:978–91. Disclosure of Interests: None declared